2015
DOI: 10.1039/c4cy01682c
|View full text |Cite|
|
Sign up to set email alerts
|

Sporopollenin as an efficient green support for covalent immobilization of a lipase

Abstract: Aminoalkyl functionalised sporopollenin exine capsules have been used to immobilizeCandida antarcticalipase B using a covalent diimine-based linker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Several L. clavatum SEC extraction processes have been developed involving acetolysis, mild enzymatic chemical treatments, or aggressive non-oxidative reagents 4 5 6 7 8 9 10 11 35 36 37 . However, acetone defatting, KOH reflux, and phosphoric acid reflux is preferred due to its convenience and utilization of non-toxic and inexpensive reagents 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Several L. clavatum SEC extraction processes have been developed involving acetolysis, mild enzymatic chemical treatments, or aggressive non-oxidative reagents 4 5 6 7 8 9 10 11 35 36 37 . However, acetone defatting, KOH reflux, and phosphoric acid reflux is preferred due to its convenience and utilization of non-toxic and inexpensive reagents 7 .…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] It was suggested that harsh chemical extraction can denature sporopollenin, 9 therefore, possible structure and/or morphology alternations have to be taken into account when one makes a comparison between empty sporopollenin originated from different plant species and extracted through different protocols. Due to their resilience, consistency in size and unique morphology, sporopollenin have recently attracted intriguing attention for a wide range of applications acting as either microparticles (as solid support) [10][11][12][13][14][15][16] or microcapsules (for diverse encapsulation of materials). 3,[17][18][19][20][21][22] The majority of research concerning sporopollenin has arisen from the thickshelled ($1.5 mm) S-type species of Lycopodium clavatum L. spores (common club moss or ground pine).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In addition, the core removal produces allergen-free sporopollenin having a large cage ready for encapsulation. 7 Due to its remarkable resilience, biocompatibility, uniformity in size and abundancy, sporopollenin has recently gained intriguing attention in different potential applications acting as either microparticles (as a solid support) [8][9][10][11][12][13][14] or microcapsules (for various encapsulations of materials). 2,7,[15][16][17][18] The majority of research involving sporopollenin has utilised the thick-shelled ($1.5 mm) S-type species of Lycopodium clavatum L. spores (common club moss).…”
Section: Introductionmentioning
confidence: 99%